Perlindungan Hukum terhadap Kreditur Pemegang Jaminan Fidusia yang Dipindah Tangankan - I Made Suarja; Simon Nahak; I Ketut Widia (Warmadewa Press, 2020)
This research was conducted based on fiduciary guarantee of execution provided for in Article 29 of Act No. 42 of the year 1999 about Fiduciary Guarantee stating that the fiduciary guarantee execution can be carried out by means of the execution of the title eksekutorial, the distribution of sale through the society, or sale under the hand with the consent of both parties. However, in practice when it will do the execution of fiduciary guarantee, guarantee that turned out to be transferable and controlled by third parties without the consent of the borrower. Formulation of the problem in this study was 1. The requirements are to be met by the lender in order to have the power of doing execution in granting credit Guarantee Chattels? 2. How is the legal protection for the lender that guarantees Fiduciary transferable? The purpose of the research to know the procedure of obtaining legal protection for holders of a Fiduciary which is transferable. The theory is a theory of legal certainty and the protection of the law. This type of research approach with normative approach legislation and the approach to the case. The first discussion about the terms of execution of fiduciary guarantee and second set of laws regarding a lender to Fiduciary redirected. The result of the research showed that if not created by notariil and registered office at Fiduciary, then their execution procedures can only be done with the setting of the ruling of the District Court. Procedures and procedures binding guarantee of fiduciary fiduciary registration procedures on Fiduciary Office, are not set or are not found in detail in the Law Number 42 Year 1999.